Deep Learning-Based Sleep Stage Classification Using EEG - Arani, Mehdi Shah Poori (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Classification of sleep stages is an essential area of research that helps develop treatments for people with sleep disorders. According to common sleep stage criteria, sleep is divided into six different stages: Wakeful sleep (W), REM (rapid eye movement) sleep, and non-REM sleep (S1-S4). Sleep processing can be performed by analyzing electroencephalogram (EEG) signals in a 30-second cycle (epoch). These stages are chosen and established on an analysis of brain workouts during sleep. This reveals a clear pattern that characterizes each stage. Sleep deprivation can cause various illnesses, including obesity, heart disease, diabetes, and reduced life expectancy [2]. Sleep professionals usually classify sleep stages into polysomnography (PSG) signals. Polysomnography consists of an electroencephalogram (EEG), electro-oculogram (EOG), electromyogram (EMG), and electrocardiogram (ECG) [2]. In addition, one category of such classifiers, Deep Learning (DL) based EEG signal classification, is used to classify sleep stages. The treatise includes an analysis of the performance of the considered methods of sleep grading. In addition, the strengths and weaknesses of classical and deep learning-based sleep staging methods will be explored. In addition, we compared standard classification with the data fusion methods with their accuracy.

ÖZ: Uyku aşamalarının sınıflandırılması, uyku bozukluğu olan kişiler için tedavilerin geliştirilmesine yardımcı olan önemli bir araştırma alanıdır. Yaygın uyku evresi kriterlerine göre uyku altı farklı evreye ayrılır: uyanık uyku (W), REM (hızlı göz hareketi) uykusu ve REM olmayan uyku (S1-S4). Uyku işleme, bir elektroensefalogram (EEG) analiz edilerek gerçekleştirilebilir. 30 saniyelik bir döngüde (dönem) sinyaller. Bu aşamalar, uyku sırasındaki beyin egzersizlerinin analizine göre seçilir ve kurulur. Bu, her aşamayı karakterize eden net bir modeli ortaya çıkarır. Uyku yoksunluğu, obezite, kalp hastalığı ve diyabet gibi çeşitli hastalıklara neden olarak yaşam beklentisini azaltabilir [2]. Uyku uzmanları genellikle uyku aşamalarını polisomnografi (PSG) olarak sınıflandırır. Polisomnografi bir elektroensefalogram (EEG), electro-oculogram (EOG), elektromiyogram (EMG) ve elektrokardiyogramdan (EKG) oluşur [2]. Bu görev, uyku aşamalarını sınıflandırmak için EEG sinyallerini kullanır. Sinyal işleme teknikleri, Veri birleştirme yöntemi gibi standart sınıflandırıcılarda gerekli işlevselliği çıkarır. Ayrıca uyku evrelerini sınıflandırmak için son teknoloji ürünü derin öğrenme tabanlı EEG sinyal sınıflandırması kullanılmaktadır. Tez, dikkate alınan uyku derecelendirme yöntemlerinin performansının bir analizini içerir. Ayrıca klasik ve derin öğrenmeye dayalı uyku evreleme yöntemlerinin güçlü ve zayıf yönleri keşfedilecektir. Ek olarak, standart sınıflandırma ile veri birleştirme yöntemlerini doğrulukları açısından karşılaştırdık.
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2023. Co-Supervisor: Dr. Noushin Hajarolasvad and Supervisor:Prof. Dr. Hasan Demirel
Keywords: Thesis Tez